2012
DOI: 10.1016/j.jmbbm.2012.03.013
|View full text |Cite
|
Sign up to set email alerts
|

New insights into hard phases of CoCrMo metal-on-metal hip replacements

Abstract: The microstructural and mechanical properties of the hard phases in CoCrMo prosthetic alloys in both cast and wrought conditions were examined using transmission electron microscopy and nanoindentation. Besides the known carbides of M23C6-type (M=Cr, Mo, Co) and M6C-type which are formed by either eutectic solidification or precipitation, a new mixed-phase hard constituent has been found in the cast alloys, which is composed of ~100 nm fine grains. The nanosized grains were identified to be mostly of M23C6 typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 48 publications
2
47
0
Order By: Relevance
“…6(a)) through the three-body abrasion. The higher hardness, 29) i.e., slower wear rate, and higher Young's modulus of precipitates as compared to the metallic matrix led their detachment during wear tests in Kokubo solution. The formation of the cavity and discontinuous groove did not depend on the phase of precipitates, which suggests that the difference of hardness and Young's modulus between precipitates and metallic matrix are dominant in cavity and discontinuous groove formation.…”
Section: Formation Of Cavities and Discontinuous Groovesmentioning
confidence: 99%
“…6(a)) through the three-body abrasion. The higher hardness, 29) i.e., slower wear rate, and higher Young's modulus of precipitates as compared to the metallic matrix led their detachment during wear tests in Kokubo solution. The formation of the cavity and discontinuous groove did not depend on the phase of precipitates, which suggests that the difference of hardness and Young's modulus between precipitates and metallic matrix are dominant in cavity and discontinuous groove formation.…”
Section: Formation Of Cavities and Discontinuous Groovesmentioning
confidence: 99%
“…For one, there is a severe deficit of standardization in the orthopedic industry. Unlike the high-performance alloys used in the aerospace industry, where every processing step is precisely controlled and standardized, the material standards often cited by prosthesis manufacturers to regulatory bodies and physicians are vague and only specify compositional bounds and lower limits on mechanical properties [16].…”
Section: Modular Total Hip Prostheses: the New Optimization Challengementioning
confidence: 99%
“…However, the potential difference between passivated cobalt and depassivated titanium has been reported by various groups to be between 600mV[44] and an astonishing 3.5V [59], depending on the medium tested. A scenario where passivated cobalt exists alongside depassivated titanium is conceivable given the higher bulk hardness of Co-Cr and the even harder carbides present in as-cast and HC wrought Co-Cr [16]. Through micromotion these carbide asperites are more than capable of disrupting the softer titanium oxide layer[60].…”
mentioning
confidence: 99%
“…Fine carbide precipitates within the grains can increase the strength, whereas coarse carbides at grain boundaries can embrittle the material. Further, the findings of Liao et al indicated that the homogeneity of the carbides in CoCrMo is dependent on the cooling rate in the solidification process, with the higher cooling rate favouring the formation of more homogeneous and harder carbides [47]. The CoCrMo alloy underwent rapid cycles of melting and solidification processes during the laser remelting.…”
Section: Surface Phase Structure Analysismentioning
confidence: 99%